The analysis of information needs in agriculture - Zinkevičienė, Julija (Knygotyra, 1990)
The article is devoted to the groups of information users in agriculture and to the structure of their information needs. The methods of their analysis are discussed. The data and the results of a questionnaire survey conducted at different levels of the agricultural information system in Lithuania are presented. The aim of this survey was to find out how data from mechanical information carriers are used. Statistical material is analyzed according to the main groups of agricultural specialists: scientists and producers. The received results enable the following statement: agricultural specialists are not satisfied with traditional information methods; however, they do not fully utilize new types of information due to unsatisfactory promotion, a shortage of technical devices, and a lack of knowledge in the information field.